Overconsumption of Stevia rebaudiana and reproductive capacity - Kruse, Maria Sol (2024)
Recently, sucrose in food and beverages has been replaced by non-caloric sweeteners. Among them is stevia, derived from the plant Stevia rebaudiana Bertoni (Asteraceae), which is native to the tropical region of South America. Although there is controversy surrounding its consumption, several studies suggest that stevia affects reproductive capacity, while others highlight its beneficial properties. In previous studies, we observed that stevia administration in female rats (F) induces changes in the estrous cycle, pregnancy capacity, litter size, and offspring survival.